Effect of hydrophobicity and charge separation on the antifouling properties of surface-tethered zwitterionic peptides - Li, Chuanxi (2021)
Zwitterionic peptides emerge as a class of highly effective antifouling materials in a wide range of applications such as biosensor, biomedical devices, and implants. We incorporated neutral amino acid spacers with different hydrophobicities, including serine (Ser), glycine (Gly), and leucine (Leu), into zwitterionic peptides with KE repeating units and investigated the structure and antifouling performance of the zwitterionic peptide brushes using surface plasma resonance (SPR), surface force apparatus (SFA), and all atomistic molecular dynamics (MD) simulation techniques. Our results demonstrate that the hydrophilicity of neutral spacers alters the structure and antifouling performance of the peptide-modified surface. Hydrophilic Ser inserted peptides reduced the interaction between the peptide monolayer and protein foulants while hydrophobic Leu significantly increased the protein adhesion. SFA force measurements shows that the presence of more spacers would increase the adhesion between the peptide monolayer and the modeling foulant lysozyme, especially for the hydrophobic spacers. MD simulations reveal that hydrophilic Ser spacers retain the hydrophilicity of the peptide monolayer and improve the antifouling performance, and Gly spacers give rise to more inter-chain crosslinks. Leu spacers result in a more hydrophobic peptide monolayer which lead to dehydration of the peptide monolayer and reduces the antifouling performances.